The next generation. (13th October 2016) - CHURCH, KENNETH WARD
Abstract: I'm sure you want me to tell you about the next new emerging trend, but I'm not going to do that. It is much easier to suggest where trends come from (the next generation), and how to distinguish passing fads (bubbles) from emerging trends. Young people are often the early adopters, the first to see what is about to happen, but most people don't see what's coming until well after the fact. Those with the most to lose (the establishment) tend to be the most resistant to change.